Efeitos do computador, da internet e do celular na comunicação escrita entre surdos - Cônsolo, Adriane Treitero (2012)
This research goal is to study about communication and information technologies applied in deaf education. To this end, we started tracing certain aspects of the historical course of the deaf in society, presenting difficulties over time to be inserted and accepted in society. This research is fundamented in the process and methods education investigation for the deaf students in the history. We also sought to show that the development of reading and writing skills were very relevant issues for the individual deaf begin the process of integration in society through written language. Later we discussed the question of breakthrough communication technologies and information and how this technology can enhance the living and social interaction among deaf people in society in which we live. All this teaching methodologies applied in the school. For the realization this research we use bibliographic references and field research in a deaf bilingual school called EMEBS Helen Keller. The searches were applied using interviews with teachers and questionnaires with closed to deaf students. And we concluded that the technology is well planned and employed can be an important resource for the teaching and learning of deaf students